Building the Character of Pancasila Students with Multicultural Awareness: Diklat Guru Merdeka Penuh Inovasi - Usmawati, Eny; Rakhmat, Cece; Ahman; LN, Syamsu Yusuf; Irawan, Andi Wahyu (Universitas Pendidikan Ganesha, 2025)
Multicultural Education plays a role in shaping the character of Pancasila students by instilling an attitude of tolerance, togetherness, and respect for diversity. This study aims to analyze the role of multicultural Education in building the character of Pancasila students, with a focus on tolerance, togetherness, and respect for diversity. This study evaluates the implementation and impact of the Diklat Guru Merdeka Penuh Inovasi Program. This study uses a qualitative approach with descriptive methods to gain an in-depth understanding of the program's Influence. This study used a purposive sampling approach, selecting participants who were actively involved in the training program. The sample consisted of teachers, students, program coordinators, and trainers. Data collection methods were through observation and interviews. The research instrument was a questionnaire. Data analysis techniques used descriptive qualitative analysis. The results of the study indicate that students' and teachers' understanding of diversity increased significantly after participating in this program, which is reflected in an increase in attitudes of tolerance and openness to other cultures. However, challenges such as the lack of integration of multicultural values in the curriculum and obstacles in implementing inclusive learning methods remain obstacles in its implementation. Therefore, a more comprehensive strategy is needed in multicultural Education, including ongoing training for teachers to enhance their competence in teaching diversity, as well as the active participation of the school community in instilling Pancasila values through various activities that involve all elements of the school.